Online Blind Buying of Local Perfume: Reducing Uncertainty through Digital Cues - Argyanti, Talitha; Ananda Sabil Hussein; Fitri Hariana Oktaviani (Universitas Muhammadiyah Yogyakarta, 2025)
Local perfumes have increasingly entered Indonesia’s e-commerce market, yet competition remains dominated by long-established local and global brands available in physical stores. New brands that rely mainly on online distribution face a significant challenge because perfumes are sensorial products that cannot be directly experienced prior to purchase, resulting in high product uncertainty. Drawing on Uncertainty Reduction Theory, this research investigates how marketplace and social media as digital platforms through product descriptions, online reviews, and interactions with the seller shape consumers’ intention to blind buy local perfumes online, while also examining the mediating role of perceived product uncertainty. A quantitative explanatory design was employed, using an online survey of 306 consumers with prior blind buying experience of local perfumes through PLS-SEM. The findings reveal that product descriptions and perceived product uncertainty significantly drive blind buying intention, whereas online reviews and interactions with the seller do not exert a direct effect. All three information cues significantly influence perceived product uncertainty, and mediation analysis indicates that seller interactions indirectly enhance blind buying intention via reduced perceived product uncertainty. These results extend the application of Uncertainty Reduction Theory by highlighting the mediating role of perceived product uncertainty in the context of online perfume purchases.